2021
DOI: 10.2147/copd.s277523
|View full text |Cite
|
Sign up to set email alerts
|

How to Assess Breathlessness in Chronic Obstructive Pulmonary Disease

Abstract: Activity-related breathlessness is the most problematic symptom of chronic obstructive pulmonary disease (COPD), arising from complex interactions between peripheral pathophysiology (both pulmonary and non-pulmonary) and central perceptual processing. To capture information on the breathlessness experienced by people with COPD, many different instruments exist, which vary in applicability depending on the purpose and context of assessment. We reviewed common breathlessness assessment instruments, providing rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 128 publications
(234 reference statements)
1
28
0
Order By: Relevance
“…The Borg rating of the perceived exertion scale (RPE scale) is a frequently used quantitative measure of perceived exertion during physical activity, useful to assess the subjective intensity of a workout session. In medicine, this is considered a reliable marker for clinical diagnosis of breathlessness and dyspnea, chest pain, angina, and musculo-skeletal pain [31].…”
Section: Mild Exercise Independently Of Administered Po 2 Does Not Affect the Maximal Oxygen Uptake Although Hypoxia Significantly Affecmentioning
confidence: 99%
“…The Borg rating of the perceived exertion scale (RPE scale) is a frequently used quantitative measure of perceived exertion during physical activity, useful to assess the subjective intensity of a workout session. In medicine, this is considered a reliable marker for clinical diagnosis of breathlessness and dyspnea, chest pain, angina, and musculo-skeletal pain [31].…”
Section: Mild Exercise Independently Of Administered Po 2 Does Not Affect the Maximal Oxygen Uptake Although Hypoxia Significantly Affecmentioning
confidence: 99%
“…Notably, the mMRC is an important independent predictor of 1-and 5-year mortality in COPD patients [25] with a study showing mMRC to be a better predictor of death than airway obstruction [26][27][28][29]. For this reason, GOLD 2020 recommends the use of the mMRC for categorizing COPD burden and guiding its management [2,30]. Furthermore, a domain-level analysis of Patient-Reported Outcomes (PRO) measures showed that breathlessness and its impact on patients were the most interpreted reported domains [31].…”
Section: Discussionmentioning
confidence: 99%
“…(3) Standardized instructions and procedures (to optimize repeatability and validity of the performance and/or ratings) (4) Assessment of breathlessness by self-report using a validated scale (as the sensation cannot be accurately inferred from proxies or biomarkers as of yet). Suitable scales may be a Borg 0-10 (CR10) scale, 0-10 NRS, or 0-100 VAS [18]. (5) Reliability and validity for the population and setting of use (6) Acceptable burden, requirements and costs for implementation…”
Section: What Characterises a Good Test?mentioning
confidence: 99%
“…Activity and function is often limited by the level of breathlessness (‘symptom threshold’). An apt illustration is during symptom-limited exercise testing, such as cardiopulmonary exercise testing (CPET) or 6-min walk test, where the level of breathlessness at the end of the test (the tolerated level) is quite similar between people – and cannot even readily distinguish healthy people from those with severe disease [ 12 , 17 , 18 ]. However, the level of exertion (workload or power output) needed to provoke that symptom level differ markedly from health to people with increasing disease severity and deconditioning [ 19 ].…”
Section: Why Is Standardized Testing Needed?mentioning
confidence: 99%